Identification of autoantibodies in human plasma recognizing an apoB-100 LDL receptor binding site peptide - Gunilla Nordin Fredrikson; Göran Berglund; Ragnar Alm; Jan-Åke Nilsson; Prediman K. Shah; Jan Nilsson (Journal of Lipid Research, 2006)
The aim of this study was to test the hypothesis that autoantibodies recognize amino acid sequences in the LDL receptor binding region of apolipoprotein B-100 (apoB-100). Autoantibodies against an unmodified or malondialdehyde (MDA)-modified LDL receptor binding site peptide were determined by ELISA in baseline plasma samples of 78 cases with coronary events and 149 matched controls recruited from the prospective Malmö Diet Cancer Study. IgG and IgM recognizing this peptide were detected in all subjects but did not differ between cases and controls. Inverse associations were observed between IgG against the native binding site and plasma oxidized LDL (r = −0.21, P < 0.005), but there were no significant associations with total or LDL cholesterol levels. In univariate analyses, inverse associations were found between baseline carotid intima-media thickness and IgG against the MDA-modified binding site (r = −0.14, P < 0.05), but this association was lost when controlling for other major cardiovascular risk factors. Specificity studies demonstrated that the binding of autoantibodies to these sequences could be inhibited by oxidized but not by native LDL. Autoantibodies recognizing the LDL receptor binding site in apoB-100 are frequently expressed. Their association with plasma oxidized LDL suggests that they have been generated in response to breakdown products of LDL oxidation, but their influence on cholesterol metabolism and the development of atherosclerosis appears limited.